Field measurements of the harvestable power potentiality of an off-road sport-utility vehicle. (July 2021) - Abdelkareem, Mohamed A.A.; Xu, Lin; Jing, Xingjian; Eldaly, Abdelrahman B.M.; Zou, Junyi; Kamal Ahmed Ali, Mohamed
Graphical abstract: Highlights: Energy harvesting potentiality of an off-road SUV was estimated experimentally for off-road and city-road sites. The power dissipation per damper on unpaved off-road segments is in the range of 30–334 W. The shock absorber traditionally dissipated an average power of 3–25 W of the paved city-road tracks. The off-road vehicle dissipated up to 12 times more power on off-road tracks than on city-roads. The power dissipated during rebound stroke is 6 times what is dissipated in the compression cycle. Abstract: The energy-harvesting, which is traditionally dissipated during the damping of the passive telescopic damper of an off-road sport-utility vehicle (SUV), was experimentally analyzed and quantified in this study. Thereafter, the following real-road driving scenarios were proposed at 10–40 km/h: (a) off-road and (b) city-road driving. The study also includes measurements of the power dissipations in the compression and rebound phases because some energy harvesters only recover energy in one phase. Thus, the rear-right suspension was equipped with acceleration sensors. The shock displacement was also recorded for the complete analyses and comparison of the dynamics and energy-harvesting during the jounce and rebound vibrations. The results indicated that the damper dissipated average powers of 30–334 and 3–25 W at 10–40 km/h on the off-road and city-road fields, respectively. The damper dissipated six times more energy in the rebound phase than in the compression phase. This harvested power could be employed to drive low-power electronics.